Association of anthropometric measures and cardiovascular risk factors in children and adolescents: Findings from the Aboriginal Birth Cohort study. - Angela Gialamas; Angela Kinnell; Murthy N Mittinty; Belinda Davison; Gurmeet Singh; John Lynch (PLoS ONE)
This study examined the association of anthropometric measures including height, leg length, trunk length and body mass index (BMI) at 11 and 18 years with systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol, low-density lipoprotein cholesterol (LDL-c) and high-density lipoprotein cholesterol (HDL-c) at 11 and 18 years. We analysed data from 661 participants from the Aboriginal Birth Cohort study-a longitudinal study based in the Northern Territory, Australia. Associations between anthropometric measures and cardiovascular risk factors were investigated in linear regression analyses adjusted for confounding, with imputation for missing data. In adjusted analyses, increasing leg length [males: 0.47mmHg/cm (0.23, 0.72); females: 0.50mmHg/cm (0.18, 0.83)], trunk length [males: 0.50mmHg/cm (0.28, 0.73); females: 0.57mmHg/cm (0.33, 0.81)] and height [males: 0.32mmHg/cm (0.16, 0.48); females: 0.32mmHg/cm (0.12, 0.52)] at 11 years was associated with higher SBP at 11 years. When these exposures were measured at 18 years the effect on SBP at 18 years had attenuated, and only increased trunk length was associated with higher SBP at 18 years for both sexes [males: 0.46mmHg/cm (0.05, 0.87); females: 0.69mmHg/cm (0.30, 1.08)]. We observed little association between height, leg length and trunk length and DBP, total cholesterol, LDL-c and HDL-c. Increased BMI was associated with elevated SBP and DBP at 11 and 18 years. Our findings suggest that height, leg length, and trunk length measured at 11 and 18 years was generally not associated with cardiovascular risk factors at 11 and 18 years. However, greater childhood BMI was associated with higher blood pressure and this association persisted into adolescence. This study contributes to the limited body of evidence on the association between measures of early anthropometry and cardiovascular risk among the Australian Aboriginal population.